1998
DOI: 10.1046/j.1523-1755.1998.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Diminished linear growth during intermittent calcitriol therapy in children undergoing CCPD

Abstract: Daily calcitriol therapy has been reported to improve linear growth in children with renal bone disease, and 1,25-dihydroxyvitamin D is a key regultor of chondrocyte proliferation and differentiation. Whereas large intermittent doses of calcitriol can lower serum parathyroid hormone (PTH) levels and reverse the skeletal changes of secondary hyperparathyroidism, the impact of intermittent calcitriol therapy on linear growth in children is not known. Thus, we studied 16 pre-pubertal patients with bone biopsy-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 155 publications
(130 citation statements)
references
References 26 publications
6
123
0
1
Order By: Relevance
“…Overall, the magnitude of reduction in bone formation did not differ between groups, but the decline in bone resorption was greater in the calcium-treated group, which could be consistent with a PTH-independent role of calcium in the regulation of osteoclastic activity (29). The prevention of adynamic bone has important clinical implications, because a substantial proportion of pediatric patients who were treated with calcitriol and calciumbased binders developed this lesion associated with more frequently elevated serum calcium levels and growth retardation (3,26,30). Furthermore, adynamic osteodystrophy was reported to be associated with greater degree of arterial calcifications (5).…”
Section: Discussionmentioning
confidence: 75%
“…Overall, the magnitude of reduction in bone formation did not differ between groups, but the decline in bone resorption was greater in the calcium-treated group, which could be consistent with a PTH-independent role of calcium in the regulation of osteoclastic activity (29). The prevention of adynamic bone has important clinical implications, because a substantial proportion of pediatric patients who were treated with calcitriol and calciumbased binders developed this lesion associated with more frequently elevated serum calcium levels and growth retardation (3,26,30). Furthermore, adynamic osteodystrophy was reported to be associated with greater degree of arterial calcifications (5).…”
Section: Discussionmentioning
confidence: 75%
“…All of the subjects were part of various clinical investigations to characterize the spectrum of renal osteodys-trophy in pediatric dialysis patients (3,(7)(8)(9)(10)(11); only baseline biopsies were used for the current analysis. All patients received calcium-based phosphate binders at the time of the bone biopsy, and in those treated with daily oral calcitriol, such therapy was held for 4 weeks before bone biopsy.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that intermittent calcitriol therapy combined with calcium-containing phosphate binders may adversely affect chondrocyte activity in the epiphyseal growth plate, with a consequent reduction in linear growth. Studies on the relations between adynamic bone, suppression of PTH with vitamin D therapies, and growth in children have yielded conflicting results [15][16][17].…”
Section: Histomorphometry Of Renal Osteodystrophymentioning
confidence: 99%